2021
DOI: 10.1136/jim-2020-001510
|View full text |Cite
|
Sign up to set email alerts
|

Association between Goal-Striving Stress and Rapid Kidney Function Decline among African Americans: The Jackson Heart Study

Abstract: African Americans (AAs) are disproportionately affected by kidney disease and also report higher psychosocial stressors than other racial groups. Goal-striving stress (GSS) is an understudied psychosocial stressor related to attempting to accomplish one’s life goals. Given the numerous social determinants that contribute to health inequities among AAs, stress from goal striving may also disproportionately affect the health of AAs and in particular kidney disease outcomes. The objective of this study was to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Adjei et al reported associations between stress at work/home and increased albuminuria and CKD risk [ 24 ]. Other psychosocial stress such as goal-striving stress (GSS) and stress-related disorders were associated with rapid kidney function decline (RKFD) after adjusting for demographics, health behaviors, risk factors, and the burden of discrimination [ 3 , 25 , 26 ]. In contrast, higher optimism was associated with lower odds of CKD and lower odds of RKFD [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Adjei et al reported associations between stress at work/home and increased albuminuria and CKD risk [ 24 ]. Other psychosocial stress such as goal-striving stress (GSS) and stress-related disorders were associated with rapid kidney function decline (RKFD) after adjusting for demographics, health behaviors, risk factors, and the burden of discrimination [ 3 , 25 , 26 ]. In contrast, higher optimism was associated with lower odds of CKD and lower odds of RKFD [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Articles included n = 2 cross-sectional studies [ 19 , 24 ], n = 1 retrospective cohort [ 20 ], n = 8 prospective cohort studies [ 3 , 19 , 21 , 22 , 23 , 25 , 26 , 27 , 28 ] and n = 8 animal model studies [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. The epidemiological studies included data for adults with different age distributions, ethnic compositions and who lived in both urban and rural areas.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations